واقع أخلاقيات التجارة الإلكترونية في المؤسسة الاقتصادية الج ا زئرية - بن نامة, فاطمة زهرة (Finance and Business Economies Review, 2017)
The age of internet has engendered ethical challenges for Algérien economic organizations as a consequence of an increase in the rate of competition among organizations , as the international network field isn’t subject to law and what happens there of abstract ethical principles , e-commerce has halped find a great number of business organizations that have websites through which they advertise their offers , this has increase piracy on the data concerning the standards of the survival of the organization , this has also given a chance to some people to invent new methods of intrusion and spying on the customers through the internet and other unethical practices. Algeria has various fortunes to devlopment in the field of e-commerce depend on the availability of information technology and communications and developed , The rapid global growth of electronic commerce and the growing international trend to deploy their applications do not leave Algeria's no room for hesitation in applying these trade .